Ammonium is the preferred source of nitrogen for planktonic foraminifer and their dinoflagellate symbionts. Issue 1929 (24th June 2020) - LeKieffre, Charlotte; Spero, Howard J.; Fehrenbacher, Jennifer S.; Russell, Ann D.; Ren, Haojia; Geslin, Emmanuelle; Meibom, Anders
Abstract : The symbiotic planktonic foraminifera Orbulina universa inhabits open ocean oligotrophic ecosystems where dissolved nutrients are scarce and often limit biological productivity. It has previously been proposed that O. universa meets its nitrogen (N) requirements by preying on zooplankton, and that its symbiotic dinoflagellates recycle metabolic 'waste ammonium' for their N pool. However, these conclusions were derived from bulk 15 N-enrichment experiments and model calculations, and our understanding of N assimilation and exchange between the foraminifer host cell and its symbiotic dinoflagellates remains poorly constrained. Here, we present data from pulse-chase experiments with 13 C-enriched inorganic carbon, 15 N-nitrate, and 15 N-ammonium, as well as a 13 C- and 15 N- enriched heterotrophic food source, followed by TEM (transmission electron microscopy) coupled to NanoSIMS (nanoscale secondary ion mass spectrometry) isotopic imaging to visualize and quantify C and N assimilation and translocation in the symbiotic system. High levels of 15 N-labelling were observed in the dinoflagellates and in foraminiferal organelles and cytoplasm after incubation with 15 N-ammonium, indicating efficient ammonium assimilation. Only weak 15 N-assimilation was observed after incubation with 15 N-nitrate. Feeding foraminifers with 13 C- and 15 N-labelled food resulted in dinoflagellates that were labelled with 15 N, thereby confirming the transfer of 15 N-compounds from the digestive vacuoles of the foraminifer to the symbiotic dinoflagellates, likely through recycling of ammonium. These observations are important for N isotope-based palaeoceanographic reconstructions, as they show that δ 15 N values recorded in the organic matrix in symbiotic species likely reflect ammonium recycling rather than alternative N sources, such as nitrates.